Application of Big Data in the Financial Audit Procedures - Nagytė, Kotryna; Dagilienė, Lina (Buhalterinės apskaitos teorija ir praktika, 2021)
Annotation. Big Data (BD) is one of the most commonly used terms in the modern world of business and information technology. The main features of BD (quantity, speed, and variety) introduce to unique processing of large information amounts, regardless of their scale, storage and computational complexity, analytical and statistical correlation. The significant emergence and potential use of BD has affected business accounting and financial auditing by replacing the long-used mechanical data collection and completion processes with automatic ones, comparing and searching for correlations between different structure and nature data.According to analysis, the main advantages of applying the BDA in the audit process are related to faster and more efficient execution of procedures, obtaining more detailed results, grouping and comparing data according to selected criteria. In the meantime, cons of BD application are related to the additional professional supervision requirements and the proper data analysis in order for the correct results interpretation.The paper presents the conceptual model, which shows the relationships between BDA tools and financial audit procedures. In addition, the model shows factors and risks, which have impacts on internal and external environment of clients, the applicability of specific audit procedures. It was found that the application of the model in the procedures includes testing of 5 relationships, i. e. classification, clustering, regression and time series analyses, the method of association rules and text research, visualization tool.The Aim of the Study is to identify the application of DDA tools in financial audit procedures.Research Methods: comparative and systematic analysis of the literature; content analysis; statistical data analysis; graphical analysis.Keywords: Big data, Big data Analytics, Financial Audit, Financial Audit Procedures.JEL Code: M15, M40, M42.
Keywords: Big data; Big data Analytics; Financial Audit; Financial Audit Procedures